‘De Heer God’: Een psychologische analyse van religieuze ervaring benadering - Chia, Philip Suciadi (Verbum et ecclesia, 2025)
‘The Lord God’: A psychological analysis of religious experience approach . This article claims that the narrator deliberately uses the name ‘The Lord God’. This specific use serves a psychological function within the story. The research will use the book of Jonah as a case study. Therefore, this article will use a lexical analysis of the name ‘The Lord God’ in addition to principles from the psychological analysis of religious experience to reveal the psychological intention of the author in the story. Intradisciplinary and/or interdisciplinary implications: This article combines exegetical insights from Bible studies and psychological analysis of religious experience.